Persuasion architectures: Consumer spaces, affective engineering and (criminal) harm - Kindynis, Theo (Theoretical criminology, 2021)
Drawing together recent theoretical work from both within and beyond criminology, this article considers the role of strategically designed consumer spaces in eliciting potentially criminogenic and harmful dispositions and behaviours. First, the article introduces recent work in cultural geography and urban studies, which has drawn attention to the manipulation of affect through spatial design. Second, by way of example, the article considers how such strategies are deployed in three types of consumer environments: shopping malls and retail spaces; casinos and other gambling environments; and the so-called night time economy. Third, the article engages such developments theoretically. It is suggested we rethink the distinctions and interrelationships between human subjectivity and agency and the built environment. The implications of this proposed conceptual reorientation are explored—first, for our understandings of agency, intentionality, moral responsibility and political accountability; and second, for criminological thinking around embodied difference, power and exclusion.